If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3f+9ff=4
We move all terms to the left:
3f+9ff-(4)=0
We move all terms containing f to the left, all other terms to the right
3f+9ff=4
| -799x^2-297=-218 | | -x^2+361=0 | | 7x+8=5x0 | | 15x+9=8x+44 | | 10x-9=3x-44 | | 2=1.015^4x | | 2(3-h)-6=(-5h) | | 2(4x-3)=3x-11 | | 18x-3=9x-30 | | 13x-8=4x-80 | | 3(x+5)-7=23 | | 5x+30=2×+24 | | 2x^2=3.5 | | 18x-4=10x+76 | | 14x+9=8x-27 | | 18x+7=9x-74 | | 5a-2=-9a+8 | | 12x+8=4x+72 | | 9x-6=3x-48 | | 15x+3=7x+27 | | (5,1);m=4 | | 3x+4/2=10 | | 40(x+3)=60(x-3) | | 3x^2+7=8 | | 2(x-3)+4x=-3(x-4) | | 2(3x+2)=3 | | 3x-1=5x=10 | | 9(-x+9)=36 | | (18x+2)+(17x+8)=180 | | X+-1/7x=48 | | 3y+7=5y-6 | | 2k=k-6/2 |